Recent Developments in Eco-Friendly Wood-Based Composites II - Bekhta, Pavlo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains 12 high-quality original research and reviews papers by 62 authors from 10 countries on 3 continents: Asia (China, India, Indonesia, and Malaysia), Europe (Austria, Czech Republic, Portugal, Romania, and Ukraine), and Africa (South Africa). These papers were published in a Special Issue, "Recent Developments in Eco-Friendly Wood-Based Composites II", of the journal Polymers. These papers provide examples of the most recent developments in eco-friendly wood-based composites.